SUBSTANTIVE ACCOUNTABILITY OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) IMPLEMENTATION AT PT. ANTAM TBK UBPN KOLAKA: A STAKEHOLDER PERSPECTIVE - Elvira Trifena Tandungan; Fransiskus Eduardus Daromes (AJAR, 2026)
This study aims to analyze the accountability of Environmental, Social, and Governance (ESG) implementation at PT ANTAM Tbk UBPN Kolaka based on stakeholder perceptions. The study employs a qualitative approach using an exploratory case study method through interviews, observations, and documentation involving 14 informants, as well as an analysis of PT ANTAM’s Sustainability Reports from 2022 to 2024. The findings indicate that environmental, social, and governance accountability has been implemented through environmental management, community empowerment, employee welfare, compliance, reporting, and oversight. However, several challenges remain, including dynamic environmental conditions, differences in understanding regarding community empowerment programs, and the need for procedural adjustments. Based on the concept of accountability, ESG implementation reflects the dimensions of responsibility, transparency, answerability, and enforcement. Overall, the implementation of ESG at PT ANTAM Tbk tends toward substantive accountability, as the commitments disclosed in the Sustainability Reports are supported by practices identified and described by stakeholders